2012
DOI: 10.1177/0974930612465205
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Geography and Infrastructure on Economic Development and International Business Involvement

Abstract: The objective of this article is to bring together geographic, marketing and economic perspectives to examine how far infrastructure development can offset adverse national geographies in aiding economic development and involvement in the global economy. We use LISREL structural equation modelling to investigate relationships between geography, infrastructure, economic development and country's involvement in trade and foreign direct investment. Results identify key geographic factors affecting global market i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 114 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…Similarly, many studies have found that infrastructure is a stronger determinant of growth in trade than tariff reduction (Bougheas, Demetriades, & Morgenroth, 1999). Others have noted that infrastructure in developing countries poses a significant barrier even if policy reform lists toward openness (Buys, Deichmann, & Wheeler, 2010;Edwards, 1993;Hill, Chae, & Park, 2012;Limão & Venables, 2001).…”
Section: Domestic Capacity and The Implementation Gapmentioning
confidence: 99%
“…Similarly, many studies have found that infrastructure is a stronger determinant of growth in trade than tariff reduction (Bougheas, Demetriades, & Morgenroth, 1999). Others have noted that infrastructure in developing countries poses a significant barrier even if policy reform lists toward openness (Buys, Deichmann, & Wheeler, 2010;Edwards, 1993;Hill, Chae, & Park, 2012;Limão & Venables, 2001).…”
Section: Domestic Capacity and The Implementation Gapmentioning
confidence: 99%
“…"Infrastructure is a dynamic concept, evolving and expanding to include new categories of assets that are critical for the functioning of the economy and the society"; it facilitates the day-to-day functioning of all citizens and it directly influences the quality of life of any community (Uddin et al 2013;Hill et al 2012;Newman et al 2008). Infrastructure normally comprises structures, systems, facilities and services, which serve a community in a large or small urban or rural area, to facilitate its functioning with an acceptable quality of life.…”
Section: Introductionmentioning
confidence: 99%